2008
DOI: 10.1590/s0100-06832008000500030
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de estoques totais de carbono e nitrogênio e suas frações em sistemas agrícolas implantados em argissolo vermelho-amarelo

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 19 publications
7
17
0
18
Order By: Relevance
“…Even in this management system there was no significant difference in values of C and N stocks in relation to the depths of the soil layers corroborating Maia et al (2007) that evaluated management systems in Sobral, CE, found that the values of C stock did not decrease with increasing depth. In all other management systems analyzed in this study, at a depth of 0-10 cm, the values of C and N stocks were higher, especially in NV and SV systems, corroborating Campanha et al (2009) andPinheiro et al (2007). However, in general, the total of the values of C stocks corresponding to the depth of 0-40 cm, was observed in descending sequence NV (46.46 Mg ha ).…”
Section: Resultssupporting
confidence: 90%
“…Even in this management system there was no significant difference in values of C and N stocks in relation to the depths of the soil layers corroborating Maia et al (2007) that evaluated management systems in Sobral, CE, found that the values of C stock did not decrease with increasing depth. In all other management systems analyzed in this study, at a depth of 0-10 cm, the values of C and N stocks were higher, especially in NV and SV systems, corroborating Campanha et al (2009) andPinheiro et al (2007). However, in general, the total of the values of C stocks corresponding to the depth of 0-40 cm, was observed in descending sequence NV (46.46 Mg ha ).…”
Section: Resultssupporting
confidence: 90%
“…In this line, Rossi et al (2012) studied soil management systems with the soybean crop in crop and pasture or sorghum in the off-season, in Montividiu/GO, observed an annual addition of organic residues of about 6.10 and 3.85 Mg ha -1 , respectively. This carbon fraction has been considered as the most sensitive portion to the management and to the more easily entry of decomposable compounds in the soil, found in crop residues (PORTUGAL et al, 2008;SOUZA et al, 2009;CONTE et al, 2011;VEZZANI;MIELNICZUK, 2011). Thus, it can be said that the till practiced in this study, represents almost all the systems adopted in the region and is promoting loss in soil quality.…”
Section: Resultsmentioning
confidence: 90%
“…no solo, o Csa associa-se às superfícies de troca dos minerais do solo, desempenhando papel importante nos processos iônicos e na ciclagem de nutrientes (rangel et al, 2008), além de ser considerada a fração mais biodegradável da mos e a principal fonte de C para os microrganismos (marschner & Kalbitz, 2003). normalmente, os teores de Csa em solo são baixos, podendo significar maior dificuldade no ataque inicial por parte das enzimas produzidas pelos microrganismos (Portugal et al, 2008).…”
Section: Frações De Carbono Orgânico De Um Latossolounclassified